The modern C# challenge : become an expert C# programmer by solving interesting programming problems - Stephens, Rod, 1961- (Packt Publishing, 2018)
Learn advanced C# concepts and techniques such as building caches, cryptography, and parallel programming by solving interesting programming challenges Key Features Gain useful insights on advanced C# programming topics and APIs Use locking and cached values to solve parallel problems Take advantage of .NET's cryptographic tools to encrypt and decrypt strings Book Description C# is a multi-paradigm programming language. The Modern C# Challenge covers with aspects of the .NET Framework such as the Task Parallel Library (TPL) and CryptoAPI. It also encourages you to explore important programming trade-offs such as time versus space or simplicity. There may be many ways to solve a problem and there is often no single right way, but some solutions are definitely better than others. This book has combined these solutions to help you solve real-world problems with C#. In addition to describing programming trade-offs, The Modern C# Challenge will help you build a useful toolkit of techniques such as value caching, statistical analysis, and geometric algorithms. By the end of this book, you will have walked through challenges in C# and explored the .NET Framework in order to develop program logic for real-world applications. What you will learn Perform statistical calculations such as finding the standard deviation Find combinations and permutations Search directories for files matching patterns using LINQ and PLINQ Find areas of polygons using geometric operations Randomize arrays and lists with extension methods Explore the filesystem to find duplicate files Simulate complex systems and implement equality in a class Use cryptographic techniques to encrypt and decrypt strings and files Who this book is for The Modern C# Challenge is for all C# developers of different abilities wanting to solve real-world problems. There are problems for everyone at any level of expertise in C#